Rhizogenesis in black raspberry stem cuttings: interaction between substrates and lesions at the base of the cuttings - Villa, Fabíola; Silva, Luciana Sabini da; Silva, Giordana Menegazzo da; Silva, Daniel Fernandes da; Friederich, Jussara Carla Conti; Cavalcante, Mateus Lopes Borduqui (Scientia Agraria Paranaensis, 2022)
The black raspberry tree has a great potential for cultivation in Brazil, as it produces large amounts of fruit, intended mainly for the processing of fine products. However, its propagation is an obstacle to the establishment of commercial plantations. Given the above, the objective of the present work was to evaluate rhizogenesis in stem cuttings, with the interaction between substrates and types of basal cuts. The experiment was conducted in a screened condition in the Institution itself. Stem cuttings were taken from mother plants in the orchard of the experimental farm. The experimental design used in the experiment was randomized blocks, consisting of a 4x2 factorial scheme, with four substrates (sand, rice husks, commercial substrate and earth) x two basal cuts (straight and bevel). After thirty days, the percentage of rooted cuttings (%), average number of roots and shoots per cutting, length of the largest root (cm) and fresh and dry biomass of the shoot and root system (g) were evaluated. Black raspberry can be propagated asexually, with cuttings without injuries at the base and rooted in gully soil or Plantmax®.